New Behaviours and Digitalisation for Sustainable Mobility, Mobility as a Service (MaaS). - Mazzoncini, Renato; Somaschini, Claudio; Longo, Michela (Springer, 2020)
This chapter will deal with changes in the behaviour of city dwellers and digital technologies which can facilitate such behaviour. Mass transportation must certainly remain the backbone of local public transport, both in terms of travel within cities and for that towards cities. However, this chapter will focus on the transformations which are taking place and which will have to be favoured in order to reduce and optimise private transport, a real scourge in large towns and cities. The final part of the chapter covers the concept of mobility as a service, being the evolution of the concept of ownership towards that of service.
Keywords: Nachhaltige Mobilität; Stadtverkehr; Mobilitätsverhalten; Autonomes Fahren; Digitalisierung; Verkehrsdienstleistung; Mobility-as-a-Service; Shared Mobility